On Analysis of Signal Detection in Relays Networks over Time-Varying Rayleigh Channels - Gatera, Omar; Sibomana, Louis; Ilhan, Haci; Kayran, Ahmet H. (IEEE, 2019)
Signal detection has been investigated in various papers due to the limited capability of receiver to recover the transmitted signals corrupted by noise and other interferences. In addition, cascaded time-varying channels are other impairments that affect the performance of signal transmission in wireless networks. Therefore, this paper evaluates the performance of Bayesian linear model ( BLM) detection receiver in recovering the transmitted signal. The main contributions are based on deriving the receiver operating characteristics ( ROC) and bit error probability over time varying multiple Rayleigh fading channels. This paper assumes that the channel state information ( CSI) is available at the destination, and original transmitted signal is corrupted by noise and other interferences. Multiple relays method is also considered due to its ability to create diversity environment that can directly mitigate the effects caused by multipath fading. The results have shown that the receiver performance decreases at high speed with respect to the number of cascading order. The receiver performance improves by increasing the number of amplify and forward ( AF) relays in the network. The findings have shown that the proposed system can be utilized in wireless relays networks such as vehicle to anything ( V2X) networks.
Keywords: time-varying Rayleigh fading channels; relays networks; receiver operating characteristics; signal detection; ENERGY DETECTION; DIVERSITY; Computer Science; Engineering; Telecommunications